Embedding Resilience in the Sustainability Balanced Scorecard: A Systematic Review and Conceptual Framework - Wiwik Mukholafatul Farida; Reni Surmayanti; Nova Sabrina (Jurnal Proaksi, 2026)
Main Purpose – This study examines the evolution of the Balanced Scorecard (BSC) into the Sustainability Balanced Scorecard (SBSC) and proposes a Resilience-Oriented SBSC (R-SBSC) that integrates sustainability performance, risk governance, and organisational adaptability.Method - A systematic literature review (SLR), guided by the PRISMA framework, was conducted on 41 SBSC-related articles published between 2020-2025. A thematic synthesis was applied to trace conceptual developments, sectoral trends, implementation patterns, and the ways resilience elements are incorporated into SBSC designs.Main Findings - The review shows a clear shift from the traditional BSC toward more contextual SBSC variants, including ESG-focused, health-inclusive, and circular SBSC models. Empirical evidence indicates improvements in strategic alignment, stakeholder trust, and sustainability performance. However, persistent challenges remain, particularly the complexity of SBSC design, indicator proliferation, and the limited explicit integration of resilience capabilities.Theory and Practical Implications - The proposed R-SBSC embeds adaptive capacity and risk intelligence within the SBSC cause–effect logic. It contributes to the development of dynamic capabilities and sustainability governance perspectives, while offering actionable guidance for managers to incorporate resilience considerations into sustainability performance management.Novelty - This study reframes the SBSC as a resilience-oriented management system through the R-SBSC model, positioning the SBSC not merely as a sustainability reporting tool but as an integrated framework for sustainability, risk, and organisational adaptation.